Stem Cells in Rotator Cuff Injuries and Reconstructions: A Systematic Review and Meta-Analysis - Liu, Fanxiao; Meng, Qingqi; Yin, Heyong; Yan, Zexing (Current Stem Cell Research & Therapy, 2019)
Background: Multiple studies have focused on stem cell-based treatments for rotator cuff disorders; however, the outcomes are not consistent. Objectives: This systematic review and meta-analysis were performed to evaluate the effects of stem cells on rotator cuff healing. Methods: A detailed search of relevant studies was conducted in three databases including Pubmed/ Medline, Cochrane library, and Embase databases, using the following keywords: “rotator cuff” or “Tissue Engineering” AND “stem cell” from inception to January 01, 2019. The standard mean difference (SMD) and 95% confidence interval (CI) for each individual study were extracted from the original studies or calculated based on relevant data and pooled to obtain integrated estimates using random effects modeling. Results: A total of 22 studies were identified. The results demonstrated that the ultimate strain in the stem cell group was significantly higher than that in the control group at 4 and 8 weeks. Muscle weight in the stem cell group was higher than the control group at 8 weeks, while no significant differences were detected at 16 weeks. The stem cell group had lower visual analog scale scores (VAS) at 1, 3, and 6 months, and higher American shoulder and elbow surgeons score (ASES) at 3 months. In addition, the walking distance, time, and speed in the stem cell group were significantly superior to those in the control group. Conclusions: This meta-analysis confirms that stem cells improved the rehabilitation of rotator cuff disorders. However, larger-scale studies are needed to further support these findings.
Keywords: Rotator cuff